Determination of benzalkonium chloride in aerosol preparations containing sodium chloride by HPLC technique - Amidžić, Bisa; Bašić, Jasmina (Archives of Pharmacy, 2022)
Benzalkonium chloride is a biocidal agent used in the pharmaceutical industry as a preservative. Benzalkonium chloride is a mixture of alkylbenzyldimethylammonium chloride, of which the three are the most important with alkyl substituents C12, C14, C16 in the quaternary ammonium salt. The purpose of this study was to develop a method for determining the content of benzalkonium chloride in aerosol preparations containing sodium chloride of different concentrations. For this purpose, the method of high performance liquid chromatography (HPLC) was used. Chromatographic analysis was performed using a Hypersil Gold CN column (4.6 mm × 250 mm, particle size 5 microns) with isocratic mobile phase consisting of 0.1 M sodium acetate solution pH 5.0 and acetonitrile in a ratio of 40:60 v/v at a flow rate of 1 mL/min. The column temperature is 25°C and the detection wavelength is 260 nm. The method was successfully validated in accordance with the AOAC guideline. The method is linear for the selected concentration range from 10 mg/L to 200 mg/L (r2 = 0.9999) for C-12, C-14 and C-16 BKC homologues. The accuracy and precision of the method was determined at the lowest and middle calibration level. The results showed good linearity in relation to the selected range, as well as accuracy and precision. The developed method is suitable for routine analysis of benzalkonium chloride in the presence of sodium chloride in various aerosol preparations, simple and does not require special preparation of samples for analysis.